Shaping Ability of XP Endo Shaper File in Curved Root Canal Models - Abdulmohsen Alfadley; Abdalrhman Alrajhi; Hamad Alissa; Faisal Alzeghaibi; Lubna Hamadah; Khalid Alfouzan; Ahmed Jamleh (Hindawi Limited, 2020)
The aim of this study was to assess the shaping ability of the XP Shaper (XPS) file in severely curved canal models under simulated body temperature and compare it with that of the WaveOne Gold (WOG) file. Ninety-six simulated root canals were equally distributed into XPS and WOG systems to be shaped by eight files each. Files were assessed under a stereomicroscope prior to canal shaping to detect deformation if any. The canals were shaped at 35 ± 1°C using the X-Smart Plus motor. Images of the canals were obtained before and after instrumentation using a stereomicroscope to measure the amount of removed resin from both the inner and outer curvature sides at apex (0 mm) and 3 mm and 6 mm from the apex. The shaping time was calculated. The data were statistically analyzed by the independent t-test at 5% significance level. The XPS and WOG systems shaped the canals in 37.0 ± 9.5 and 62.6 ± 11.3 seconds (P<0.05), respectively. At the apex level, the amount of resin removal in both sides did not show a significant difference between the tested groups (P>0.05). At 3 mm and 6 mm levels, the WOG removed more resin than XPS at both sides (P<0.05). In XPS, deformation was observed in four files: one file after the first use, one file after the fourth use, and two files after the sixth use. In WOG, two files were deformed: one file after the fifth use and one file after the sixth use. One XPS file was fractured after the sixth use. In short, XPS and WOG files can be used in shaping severely curved canals as they showed the ability to maintain the original shape with minimal transportation. Both file systems showed signs of deformation after use with a lower number of deformed files observed in WOG throughout the experiment.